2022
DOI: 10.3390/land11020224
|View full text |Cite
|
Sign up to set email alerts
|

Application of Steel Slag for Degraded Land Remediation

Abstract: Land degradation, and especially acidification, are global issues that need to be addressed. A common practice to correct this problem is the use of lime or chemical fertilisers that involve the extraction of raw materials. This study proposes a more sustainable alternative using Basic Oxygen Furnace (BOF) slag. BOF slag is the main waste from the steel industry that is usually accumulated in landfills, which also implies environmental impacts. In this study, a series of laboratory tests have been carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…Soil acidification is a key cause of land degradation (Díaz‐Piloneta et al, 2022). The pollutants causing acidification are sulphur dioxide (SO 2 ), nitrogen oxides (NO x ) and ammonia (NH 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil acidification is a key cause of land degradation (Díaz‐Piloneta et al, 2022). The pollutants causing acidification are sulphur dioxide (SO 2 ), nitrogen oxides (NO x ) and ammonia (NH 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The indicator was provided by Mapping and Assessment of Ecosystems and Their Services: An EU ecosystem assessment publication(Joint Research Centre (European Commission) et al, 2020). It was stratified using the land cover and is considered a potential LCI when the value is greater than the median of values in the same land cover class.2.2.13 | AcidificationSoil acidification is a key cause of land degradation(Díaz-Piloneta et al, 2022). The pollutants causing acidification are sulphur dioxide (SO 2 ), nitrogen oxides (NO x ) and ammonia (NH 3 ).…”
mentioning
confidence: 99%
“…Por todos son conocidas las bondades de la contruccion off site frente a la construcción convencional, proliferando una gran cantidad de empresas de construcción modular, que presentan solución al desequilibrio entre costes y prestaciones (1). La recuperación de la actividad constructora global de la última década se ha basado principalmente en la Industrialización, la gran mayoría, tratan de despuntar siguiendo alguno de los principios impulsores del mercado global: ahorro de energía y rentabilidad, limitaciones de espacio en las grandes ciudades, tendencia global a la construcción verde (2).…”
Section: Introductionunclassified
“…Mihalache et al 20 concluded that the waste resulted from secondary refinery of the steel can be use with good results in agriculture, with positive influences on the maize crop and as amendment for correction acidic soil reaction, and the slag from the steel industry brings increases of calcium and micronutrients in soil content. Fan et al 21 concluded that the use of slag as a fertilizer can decrease Cr, Cu, Pb and Zn in acidic soils and indicated that the slag could be used in PTE pollution control for plants and the environment. The researchers 22 investigated the feasibility of using BOF slag for degraded land remediation in two different ways: as liming material and as amendment nutrient source and they showed that as the slag content increases, the mobility of some basic nutrients such as Mg decreases, so an addition of more than 25% is not recommended.…”
Section: Introductionmentioning
confidence: 99%